Strengthening Aisyiyah Banguntapan 4's Understanding of Murabahah Financing as a Sustainable Sharia Economic Solution - Istianah Zainal Asyiqin; Ani Yunita; Muhammad Habibi Miftakhul Marwa; Annisabella Oktaviani; Tanu Surana (Indonesian Journal of Legal Community Engagement, 2025)
The growth of Islamic financial assets in Indonesia reached IDR 2,450.55 trillion in June 2023, with a market share of 10.94% of the total national finance. Islamic banking institutions, particularly those offering financing based on sale and purchase agreements like murabahah, are crucial in expanding financial inclusion and providing Sharia-compliant financial solutions. ‘Aisyiyah, as part of the Muhammadiyah women's movement, plays a significant role in community empowerment, including enhancing knowledge of Islamic financing. This study aims to strengthen the understanding of murabahah financing among the ‘Aisyiyah Banguntapan 4 community, particularly in addressing misconceptions and reducing reliance on usurious transactions. The implementation method in this community service activity consisted of three stages: preparation, implementation, and evaluation. The implementation stage included educational sessions in the form of material presentation, discussions, and legal analysis of murabahah financing, conducted at the partner location with 50 participants. Evaluation was carried out to assess the effectiveness and impact of the program on participants’ knowledge. Data collection methods were through interviews, surveys, and direct engagement with community members. The results indicate a notable improvement in participants' comprehension of Law No. 21 of 2008 on Sharia Banking (45.5%), MUI Fatwa on Usury (51%), DSN MUI Fatwa on Murabahah (50.5%), sharia-based economic transactions (50%), and the concept and implementation of murabahah financing (50.5%). These findings highlight the effectiveness of educational efforts in enhancing public awareness of Islamic financial principles, thereby fostering financial literacy and reducing dependence on non-sharia-compliant transactions.